2005
DOI: 10.1172/jci19935
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol targeting alters lipid raft composition and cell survival in prostate cancer cells and xenografts

Abstract: Lipid rafts are cholesterol-and sphingolipid-enriched microdomains in cell membranes that regulate phosphorylation cascades originating from membrane-bound proteins. In this study, we tested whether alteration of the cholesterol content of lipid rafts in prostate cancer (PCa) cell membranes affects cell survival mechanisms in vitro and in vivo. Simvastatin, a cholesterol synthesis inhibitor, lowered raft cholesterol content, inhibited Akt1 serine-threonine kinase (protein kinase Bα)/protein kinase B (Akt/PKB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
307
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(334 citation statements)
references
References 59 publications
20
307
3
Order By: Relevance
“…Although there is much controversy, buttressed by claims and counterclaims, in the various population-based reports of the effects of statins on cancer, recent evidence published by several groups examining large prospective series suggest that prostate cancer progression is likely to be inhibited by long-term cholesterol-lowering therapy (Platz et al, 2006;Mondul et al, 2010). These promising results in humans are in agreement with animal model data, in which cholesterol is raised or lowered and prostate tumor growth thereby promoted or inhibited, respectively (Zhuang et al, 2005;Solomon et al, 2009). Prostate cancer may be a special case, however, because recent observations from several groups indicate that tumor cells are capable of de novo androgen synthesis from cholesterol, obviating the need to acquire the hormone from the circulation.…”
supporting
confidence: 57%
“…Although there is much controversy, buttressed by claims and counterclaims, in the various population-based reports of the effects of statins on cancer, recent evidence published by several groups examining large prospective series suggest that prostate cancer progression is likely to be inhibited by long-term cholesterol-lowering therapy (Platz et al, 2006;Mondul et al, 2010). These promising results in humans are in agreement with animal model data, in which cholesterol is raised or lowered and prostate tumor growth thereby promoted or inhibited, respectively (Zhuang et al, 2005;Solomon et al, 2009). Prostate cancer may be a special case, however, because recent observations from several groups indicate that tumor cells are capable of de novo androgen synthesis from cholesterol, obviating the need to acquire the hormone from the circulation.…”
supporting
confidence: 57%
“…In agreement with this hypothesis, Zhuang et al 46 have demonstrated that a cholesterol-rich diet can accelerate tumor formation in mice engrafted with prostate cancer cell lines. Their findings suggest that increased cholesterol content of lipid rafts is associated with greater cell survival of these prostate cancer cell lines.…”
Section: Cholesterol and Cellular Proliferationmentioning
confidence: 64%
“…In prostate cancer cells, fatty acid and cholesterol synthesis pathways are highly upregulated (Rossi et al, 2003;Platz et al, 2008). In SCID mice injected with prostate cancer cells, an elevation in circulating cholesterol increases the cholesterol content of lipid rafts, alters raft-mediated downstream signaling, and promotes tumor growth (Zhuang et al, 2005). These findings suggest that novel molecules involved in cholesterol-dependent tumor progression may be identified in the lipid rafts.…”
Section: Prostate Cancermentioning
confidence: 99%
“…The mevalonate pathway, which promotes cholesterol accumulation, is highly upregulated in prostate cancers, and epidemiological studies have been performed to examine the association between high serum cholesterol and an increased risk of prostate cancer (Pelton et al, 2012). Treating prostate cancer cells with simvastatin, an inhibitor of cholesterol synthesis, lowers the cholesterol content of the plasma membrane and inhibits raft-mediated signaling related to cancer progression (Zhuang et al, 2005), while the long-term administration of statins reduces the risk of human prostate cancer (Solomon and Freeman, 2008).…”
Section: Prostate Cancermentioning
confidence: 99%